Influential Article Review - Local Business Marketing and Social Media Tactics - Greer, Van; Glover, Ramiro; Hayes, Saul (Journal of Marketing Development and Competitiveness, 2022)
This paper examines online marketing strategies. We present insights from a highly influential paper. Here are the highlights from this paper: Small businesses need to keep current and build relationships with target consumers and clients. Today, social media has become increasingly viable for CRM initiatives including new customer acquisition and loyalty programs. Based on the social exchange theory, this study determined the characteristics of small businesses (N=515) externally communicating and utilizing social media, as well as the discovering the perceptions these businesses have toward utilizing, updating, and monitoring social media sites. Research indicates that 77% of small businesses are using social media, but only 39% update these sites “as needed”. The findings led to several recommendations and questions for further research. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.